Impact of molar incisor hypomineralization on oral hygiene and gingival health in 8-15-years-old children - Türkmen, Emrah; Özükoç, Can (Wiley, 2022)
Background: This study aimed to evaluate the impact of molar incisor hypomineralization (MIH) on oral hygiene and gingival health, and to investigate the relationship between these factors and the severity of MIH. Methods: A total of 72 children (48 with MIH and 24 healthy controls) were included in the study. MIH severity was categorized into three groups:mild (n = 16), moderate (n = 16) and severe (n = 16).The modified-Quigley Hein plaque index (m-QHPI) was used to determine oral hygiene, and the gingival index (GI) and bleeding on probe (BOP) were used to determine the gingival status of each subject. The Mann–Whitney U test was used for binary comparisons and the Kruskal–Wallis test was used for multiple comparisons. Results: The m-QHPI,GI and BOP were significantly higher in all individuals with MIH compared with the control group. The m-QHPI increased with the severity of MIH (P < 0.001).The GI of the MIH-affected teeth had highly significant increases according to MIH severity (P < 0.05). The mean BOP score for the entire mouth was significantly higher in patients with severe and moderate MIH than mild MIH (P < 0.001). The mean BOP for affected teeth with moderate and severe MIH was significantly higher than the mean BOP of mildly affected teeth (P < 0.05). Conclusion: The presence and severity of MIH might be associated with increased plaque accumulation and gingival inflammation.
Keywords: Gingival Health; Molar Incisor Hypomineralization; Oral Hygiene; Paediatric Dentistry; Periodontology